Characterization of flicker noise in sub-micron NMOS device - Myo Thant Win. (2008)
Nowadays MOS device sizes and signal levels are aggressively scaled down, the low-frequency noise (LFN) properties become increasingly important. This is because the signals are no longer significantly higher than the LFN, especially since the LFN level increases significantly as the device's size is scaled down. The aforementioned reasons have motivated our investigation of 1/f noise in MOS transistor. In this project, the characterization of low frequency noise in n-channel metal-oxide semiconductor (NMOS) devices fabricated using minimum channel length of 0.13^m technologies are experimentally evaluated and compared.